Assessment of a raffia fiber-based biosorbent in hydrocarbon sorption - Silva, Tomás Heineck Rodrigues Só e; Bueno, Vitória Damaceno; Andrade, Matheus Rodrigues de; Vieira, Michele Oliveira; Monteiro, Wesley Formentin; Mveh, Jean de Dieu Briand Minsongui; Schütz, Marta Kerber; Lima, Jeane Estela Ayres de; Ligabue, Rosane Angélica (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Oil spills and discharges of petroleum products have severely polluted aquatic ecosystems, oceans, rivers, groundwater and even soil. In August 2019, more than 2,000 km of the northeast and southeast coast of Brazil were struck by a major oil spill in the country’s largest ever environmental disaster. Spill remediation is a significant environmental challenge and the economic and socioenvironmental impacts of these events are diverse. Oil spills in oceans and rivers severely affect the fishing and tourism industries of the areas in question, with damage including severe short and long-term effects on plants and animals, such as respiratory and digestive disorders, reduced growth and reproductive capacity as well as weakened immunity due to the bioaccumulation of toxic contaminants. There are several proposed strategies for removing crude oil and petroleum products from surface water. Contaminated areas can be remediated in-situ or ex-situ, with the former considered the best option in terms of cost and efficiency. In this respect, absorbent materials obtained from biomass have received widespread attention due to their ease of use, buoyancy and low cost. Raffia is a natural fiber abundant in eastern Africa with excellent physical properties, such as low specific weight, good liquid sorption and low conductivity. As such, the present study investigated the application of raffia fiber with different particle sizes (< 300 µm, 300 - 850 µm, 850 - 1000 µm, 1000 - 1400 µm and 1400 - 2000 µm) and fiber/hydrocarbon ratios (1, 2, 3 and 4% w/v) as an absorbent for hydrocarbons, using n-heptane as a model molecule. Microscopic analysis of micronized raffia fiber indicated the presence of honeycomb-shaped cells with well-defined borders and an irregular geometry. These honeycomb structures are preserved, especially in large particle size ranges. Among the granulometries assessed, the highest sorption capacities were obtained for 1000 to 1400 µm raffia fibers, suggesting that honeycomb-shaped structures favor hydrocarbon sorption. Additionally, the fact that smaller particles do not require micronization is economically beneficial and facilitates application of the absorbent material to remediate hydrocarbon-contaminated areas. The results obtained under the conditions studied indicate that sorption capacity increases as the absorbent content rises. Comparison of fiber contents of 1% and 3% w/v for 1000 - 1400 µm particles showed an increase of approximately 43% in sorption capacity when content rose to 3% w/v. The results of the present study demonstrate the potential of natural raffia fiber as an alternative absorbent for hydrocarbons.